Co-cultivation of Daphnia magna (Straus) and Desmodesmus armatus (chod.) Hegew. in recirculating aquaculture system wastewater - Чебан, Лариса (My University, 2018)
The study focused on the development of co-cultivation schemes for Daphnia magna (Straus) and Desmodesmus armatus (Chod.) Hegew. Wastewater from a recirculating aquaculture system (RAS) was used as a medium for co-cultivation. Three schemes for D. magna and algae co-cultivation that differed in the timing of the introduction of Daphnia into the system were tested. Initially, D. armatus algae were cultivated to the exponential growth phase until cell numbers reached 5 × 104 cell × l-1. This algal culture was introduced into the system for joint cultivation. D. magna was added immediately on the same day or three or six days after the algae. The number of D. magna individuals and the number of D. armatus cells were analyzed. It was established that the optimal scheme is the simultaneous introduction of algae and crustaceans into the cultivating system. By implementing this system it was possible to increase the number and biomass of D. magna by ten times in comparison to initial values.The biochemical composition of the D. magna obtained after co-cultivation and Daphnia that was fed traditionally once every 48 h with the same algae or yeast, Saccharomyces cerevisiae, was also compared. The scheme applied for D. magna and D. armatus simultaneous co-cultivation rendered it possible to obtain a biomass of Daphnia that was characterized by a protein content of 82.5% lipids of 6.7%, and carotenoids of 15.3 mg × g-1
Keywords: Daphnia magna; Desmodesmus armatus; co-cultivation; feeding scheme; proteins; lipids; carotenoids